PENDEKATAN PROBLEM POSING DALAM PEMBELAJARAN MATEMATIKA - Siregar, Nur Fauziah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2016)
Problem posing in learning mathematics gives more chances for student to achieve, change, and create new mathematics idea through active cooperation in certain discussions. Learning mathematics through problem posing, the students are seen to be active and creative in case of their competences in developing problems/questions of mathematics, understanding as well as exploring information from the problems/questions and posing mathematics problem with is solution. Then, through this problem posing approach, students’ activity and interaction in sharing idea with other students and their teacher could be improved; so that learning activity gives more meaning and understanding for students toward mathematic learning.